Analysis of the Ground Level Enhancement GLE 60 on 15 April 2001, and Its Space Weather Effects: Comparison With Dosimetric Measurements - N. Larsen; A. L. Mishev (Space Weather)
Abstract As a result of notable solar activity observed in April 2001, one of the strongest ground level enhancements (GLE) of solar cycle 23 occurred, namely GLE # 60 on 15 April 2001. In this paper, we derived the spectral and angular characteristics, and apparent source position of the solar protons during the GLE # 60, using a verified by direct measurements model and employing the calibrated neutron monitor yield function. Subsequently, employing the updated and verified by balloon measurements dosimetric model: Oulu CRAC:DOMO (Cosmic Ray Atmospheric Cascade: Dosimetric Model) we computed the dose rates throughout the event at several altitudes using the obtained spectra as an input. A global map of the ambient dose at an altitude of 35 kft is computed. A comparison with direct dosimetric measurements obtained by a Liulin device during an intercontinental flight is performed and good agreement is achieved.